Some aspects of production costs in Irish agriculture, as illustrated by the cost of producing sugar beet - Costello, M. J. (Statistical and Social Inquiry Society of Ireland, 1954)
For reasons which are mainly historical but in part arise from our political evolution since 1922, very little is known of the actual costs of production and marketing on Irish farms. We have more data about the economic aspects of Irish agriculture in the 18th century than in the 20th. While an ever increasing volume of publications about agricultural economics is emerging from Universities, Research Establishments and Government Institutions abroad, similar publications about Ireland's greatest industry appear to have diminished in volume and in value since we got control of our own affairs in the Twenty-Six Counties.
Read before the Society, 26 March 1954
Keywords: Agriculture, Ireland, Production costs; Irish Sugar Company; Sugar beet, Production costs, Ireland; 314.15